Learning French at Cihan University – Sulaimaniya Case of students in the English department - Kareem Abdlurahman Othman (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
The present study is carried out during the current academic year 2018/2019, in the English department of Cihan-Sulaimani University, where the French language has been integrated into the program of the third and fourth years. It attempts to identify the perceptions of third and fourth year students learning French as a Foreign Language (FLE) at Cihan University in Iraqi Kurdistan. We tried to find out about the difficulties encountered by students learning French by exploring each other’s points of view in order to determine the nature of these difficulties. In addition, the French teachers of the school also participated in this study for the same purpose. The selected sample consisted of 30 third and fourth year students. A questionnaire has been drawn up for this study on difficulties in learning foreign languages, particularly French. Student responses were analyzed and compiled. The results of this study show that most students generally showed a positive attitude towards learning French, regardless of their difficulties. From a teacher’s point of view, the high level of learning difficulties was related to the student, the nature of the language and the school environment. This study will be beneficial for teacher training sessions and the development of their skills.